THE DIFFERENT TYPES OF INVESTORS (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
An investor is any person or other entity (such as a firm or mutual fund) who commits capital with the expectation of receiving financial returns. Investors rely on different financial instruments to earn a rate of return and accomplish important financial objectives like building retirement savings, funding a college education, or merely accumulating additional wealth over time.